KOZHEVNIKOV–RASMUSSEN’S ENCEPHALITIS. A CASE REPORT - A. S. Kotov; I. G. Rudakova; K. Yu. Mukhin; M. B. Mironov; N. E. Kvaskova; A. A. Alihanov (Русский журнал детской неврологии)
Kozhevnikov–Rasmussen's encephalitis (KRE) is a rare inflammatory brain disease characterized by severe intractable epilepsy and unilateralprogressive motor defect associated with controlateral hemispheric atrophy. Authors described clinical features, electroencephalography and magnetic resonance tomography data and course of the disease during 12 years of patient with adult onset KRE.